(untitled) (Nepal Medical College Journal, 2023)
Postoperative nausea and vomiting (PONV) is the second most common complaint in postoperative period especially in high risk surgeries like laparoscopic cholelithiasis. Many pharmacological strategies has been used for its prevention as PONV may cause adverse effects. Drugs like granisetron and dexamethasone has been used alone and in combination for the prophylaxis of PONV. We observed the adequacy and safety of the combination of these drugs by injecting granisetron (40mcg/kg) with dexamethasone (6mg) after induction of anesthesia. The total number of cases enrolled was 115. During 0-2 hours postoperatively, nausea, retching or vomiting was not seen in 110 (95.7%) of patients. Four (3.5%) patients had nausea or retching and 1 (0.9%) had vomiting episode in 30 minutes duration. During 2-6 hours, no nausea, retching or vomiting was seen in 113 (98.3%) patients and an episode of nausea was present in 2 (1.7%) cases. There was no nausea, retching or vomiting in any patient during 6-12 and 12-24 hours. The prophylactic anti-emetic therapy with combination of granisetron and dexamethasone is effective and safe during the first 24 hours in the postoperative period after laparoscopic cholecystectomy.